(untitled) (Mustansiria Dental Journal, 2018)
Teachers are believed to be the key in any educational program so they could be targeted in order to enhance the effect of dental health education. A sample of eighty eight of first year primary school children aged 6 – 7 years old were randomly chosen and allocated into two group ,control and experimental (with 44 children in each group ). Teaching staff of experimental group were submitted to oral health education program that were conducted for the children in the experimental group only. The total sample were examined using plaque index PLI (silness & Loe) & gingival index GI (Loe & silness). The first examination carried out before the program conduction and the second examination done one month after. A highly significant improvement was recorded among the children in the experimental group after the program conduction. Results of this research support the positive role of the educational programs in the improvement of dental and periodontal health. Therefore, oral health education for school children is an essential activity for promoting, establishing and marinating optimal oral health and preventing oral diseases.